La venerable Madre Ágreda: un drama con desenlace retardado: Investigaciones y problemas abiertos - Artola, Antonio M. (Alpha Omega, 2018)
Summary: The cause for the beatification of Mother Mary of Jesus of Ágreda, O.I.C. (1602-1665), has experienced high and low points in the course of its history. The author analyses the various phases in the history of the process, in which a determining role has been played by the doctrinal judgment upon her principal work, the Mistica Ciudad de Dios (The Mystical City of God, first edition, 1670), a work of Marian spirituality, which contributed in a significant way to the defence of the dogma of the Immaculate Conception. The present halt to the process of beatification is due to a letter written by the Secretary of State to the Postulator of the cause, of February, 1999, in which the book in question is recognised as being devoid of errors, but at the same time as contrasting with what is offered to us both by Sacred Scripture and by the Second Vatican Council. Hence the refusal to grant the nihil obstat for the continuation of the cause of beatification. The author analyses the letter and subsequent developments, in particular, the efforts of the Spanish episcopal conference to reactivate the cause. Key words: Mother Mary of Jesus of Ágreda, The Mystical City of God, Mariology, Immaculate Conception, Marian spirituality, beatification. Sommario: La causa di beatificazione di Madre Maria de Jesús de Ágreda O.I.C. (1602-1665), ha subito alti e bassi nel corso della storia. L’Author analizza le varie fasi storiche del processo, in cui ha giocato un ruolo determinante il giudizio dottrinale sulla sua opera principale, la Mistica Ciudad de Dios (1ª ed. 1670), una opera di spiritualità mariana che ha contribuito in modo importante alla difesa del dogma dell’Immacolata Concezione. L’attuale arresto del processo di beatificazione è dovuto a una lettera della Segreteria di Stato al Postulatore della causa, nel febbraio 1999, in cui il libro in questione è riconosciuto privo di errori, ma allo stesso tempo in contrasto con ciò che ci offre la Sacra Scrittura e la mariologia del Concilio Vaticano II. Da qui il rifiuto del nihil obstat per il proseguimento della causa di beatificazione. L’Author analizza la lettera e gli sviluppi successivi, in particolare i tentativi della Conferenza Episcopale Spagnola di riattivare la causa. Parole chiave: Madre Maria de Jesús de Ágreda, Mistica Città di Dio, Mariologia, Immacolata concezione, spiritualità mariana, beatificazione.